Wheelchair Fencing - Villiere, A.; Edwards, M.; Sahota, B.; Turner, A. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Fisan exciting, dynamic and fast paced sport practiced exclusively seated on a specific wheel- chair. The sport 1s performed both in teams and individually, where 3 weapons can be distinguished (foil, epee and sabre). To promote equity in competitions, a classification system has been established categorising athletes according their level of disability. The paucity of research in WF prevents the authors from providing specific data regarding the athletic demand of the sport. However, from the authors` empirical experience, WF is expected to tax predominantly the anaerobic energy systems. Furthermore, the wheelchair fencer is required to repetitively perform high velocity lunges; therefore, an increase in RFD of the recruited muscles would appear beneficial. Differences in biomechanical features and muscle recruitment of the lunge at increased distances are observed between fencing categories. As a result, category B athletes are predisposed to a greater injury risk. A well designed strength and conditioning program accounting for an athlete`s impairment can assist the wheelchair fencer to reach peak performance. The strength and conditioning coach working with such a population will require creativity to enhance specific WE physical attributes while promoting a safe working environment.